Coupling immunoprecipitation with multiplexed digital PCR for cell-free DNA methylation detection in small plasma volumes of early-onset colorectal cancer - Truong, Tu; Mikloska, Klara; Sum, Judith; Oberländer, Martina; von Bubnoff, Nikolas; Christiansen, Lea; Tornow, Sebastian; Derer, Stefanie; Janke, Florian; Sültmann, Holger; Zeissig, Sebastian; Linnebacher, Michael; et al. (Analytical chemistry, 2025)
Colorectal cancer (CRC) remains a major global health challenge, with an increasing incidence of early-onset cases among young adults. Targeted analysis of cell-free DNA (cfDNA) methylation in blood has emerged as a promising minimally invasive diagnostic approach. While digital PCR (dPCR) offers high sensitivity and low turnaround times, conventional bisulfite-based dPCR assays require large plasma volumes due to cfDNA degradation, limiting clinical feasibility. To overcome this limitation, we developed a bisulfite-free, low-plasma-volume assay by coupling cell-free methylated DNA immunoprecipitation (cfMeDIP) with multiplexed dPCR for methylation detection. Assays were designed for CRC targets based on publicly available bisulfite-based plasma data and optimized for native, bisulfite-untreated cfDNA. The cfMeDIP-dPCR assays were first developed and optimized on circulating tumor DNA surrogates derived from HCT116 cells and subsequently validated in a pilot study, including 32 early-onset CRC (EO-CRC) patients and 29 non-CRC individuals. Methylation ratios, defined as the proportion of methylated to total cfDNA copies per marker, served as a diagnostic indicator. Three out of four selected markers (SEPT9, KCNQ5, and C9orf50) were successfully adapted, with significantly higher methylation ratios (p ≤ 0.001) in the EO-CRC cohort. KCNQ5 demonstrated the highest diagnostic performance, achieving an 85% sensitivity at a 90% specificity, with methylation ratios correlating with the tumor stage. This study presents the first cfMeDIP-dPCR approach, demonstrating its potential as a sensitive liquid biopsy assay. Requiring only 0.5 mL of plasma, i.e., more than 20 times less than a sensitivity-matched bisulfite-based assay, cfMeDIP-dPCR facilitates clinical implementation for CRC and other diseases with epigenetic signatures.
Gesehen am 04.11.2025